A Method for Isolating and Characterizing Mesenchymal Stromal Cell‐derived Extracellular Vesicles. (11th June 2018) - Lo Sicco, Claudia; Reverberi, Daniele; Pascucci, Luisa; Tasso, Roberta
Abstract: The unit describes protocols for isolating and characterizing extracellular vesicles (EVs) derived from human adipose tissue‐derived mesenchymal stromal cells (MSCs). EVs are a mixed population of membrane‐surrounded structures with overlapping composition and size. Advances made in recent years have led to a better understanding of the biological role of EVs. In particular, they can be considered key factors responsible for MSC‐paracrine activity, mediating their anti‐inflammatory effects towards innate immune cells, such as macrophages. The topics comprise description of the MSC‐conditioned medium containing vesicles preparation, EV isolation, and characterization mainly by specifically set up flow cytometry and electron microscopy approaches, and in vitro methodologies involved in testing the EV anti‐inflammatory capacity. The procedures described here can be easily reproduced and can be employed regardless of the type of progenitor cells used to secrete EVs. © 2018 by John Wiley & Sons, Inc.